2018
DOI: 10.1186/s12985-018-1055-y
|View full text |Cite
|
Sign up to set email alerts
|

Torquetenovirus detection in exosomes enriched vesicles circulating in human plasma samples

Abstract: BackgroundTorquetenovirus (TTV) belongs to Anelloviridae family, infects nearly all people indefinitely without causing overt disease establishing a fine and successful interaction with the host. Increasing evidence have shown some human viruses exploit extracellular vesicles thereby helping viral persistence in the host. Here, the presence of TTV in extracellular vesicles circulating in human plasma was investigated.MethodsTTV DNA was quantified in plasma-derived exosomes from 122 samples collected from 97 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 44 publications
0
18
0
1
Order By: Relevance
“…Moreover, it was recently found that TTV particles can circulate in the body within exosomes (Martelli et al . 2018 ). Travelling within vesicles can promote spread of the virus by two means: it may enhance infectivity by allowing entry of TTVs in otherwise non-permissive cells, and the virus inside the exosomes may be less exposed to neutralizing antibodies (Martelli et al .…”
Section: Infection Cycle Of Avs: Genome Replication and Protein Synthmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it was recently found that TTV particles can circulate in the body within exosomes (Martelli et al . 2018 ). Travelling within vesicles can promote spread of the virus by two means: it may enhance infectivity by allowing entry of TTVs in otherwise non-permissive cells, and the virus inside the exosomes may be less exposed to neutralizing antibodies (Martelli et al .…”
Section: Infection Cycle Of Avs: Genome Replication and Protein Synthmentioning
confidence: 99%
“…Travelling within vesicles can promote spread of the virus by two means: it may enhance infectivity by allowing entry of TTVs in otherwise non-permissive cells, and the virus inside the exosomes may be less exposed to neutralizing antibodies (Martelli et al . 2018 ).…”
Section: Infection Cycle Of Avs: Genome Replication and Protein Synthmentioning
confidence: 99%
“…Exosomes, small EVs with a diameter of 20–140 nm, [ 5 ] are secreted by most cells and are abundantly present in body fluids such as blood, [ 6 ] where the exosome concentration can exceed 10 9 mL −1 . [ 7 ] Exosomal lipid bilayer membranes permit them to stably carry genetic material and protein from their cells of origin (including early stage cancer cells) [ 8,9 ] and allow exosomes to serve as ideal tools for use in monitoring cancer occurrence and progression. [ 10,11 ]…”
Section: Introductionmentioning
confidence: 99%
“…ORF1 contains hypervariable regions that are responsible for wide range of genetic variations. [ 4 ] Based on ORF1, the International Committee on Taxonomy of Viruses (ICTVs) defines three genera for human Anelloviruses, including Alpha Torque Teno, Beta Torque Teno, and Gamma Torque Teno viruses. The prototype of this family was isolated by Nishzawa et al .…”
Section: Introductionmentioning
confidence: 99%
“…Replication of these viruses occurs in various tissues, such as the liver, lymph nodes, spleen, lung, muscles, lymphocytes, and polymorphonuclear cells. [ 7 ] However, the main replication site of the virus has been reported to be in T-cell lymphocytes[ 4 ] and the replication of the virus may be performed by rolling circle mechanisms. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%